The Role Of Parents In Improving Self-Confidence Of Early Adolescents In Bahbutong Village 1 - Najwa Aulia; Nefi Darmayanti; Nur Anissa; Dwi Amalia Susilo; Ichsani Walidaini (Jurnal Multidisiplin Sahombu, 2024)
Teenager beginning is a transition period from children going to teenagers who usually occurs in the range age 10-13 years. In the phase this, child start experience Lots change physical, emotional, and social. Trust self be one of aspect study This. Trust self in adolescence currently built, so that the condition classified as low. In fact, trust self That required for teenager For to form identity positive self. And, one the influencing factors are support social parents in adolescents early. Research This use method study field, with do observation in a way direct precisely in the village Bahbutong I. Research This aiming For know How role of parents in increase trust self teenager the beginning that occurred in Bahbutong I Village for know connection between support parent social with trust self in adolescence beginning, role support parent social to trust self teenager beginning, and level trust self teenager beginning and level support parents' social. Research results This show that Parents own a very important role in help teenager beginning increase trust yourself. Here a number of role main thing that can done like Give Support Emotional, Recognizing and Appreciating Children's Potential, Giving Good Example (Role Model), Encourage Independence as well as Giving the Right Compliments.